Impact of Hypnosis Intervention in Alleviating Psychological and Physical Symptoms During Pregnancy - Beevi, Z.; Low, W.Y.; Hassan, J. (Taylor & Francis, 2016)
Physical symptoms (e.g., vomiting) and psychological symptoms (stress, anxiety, and depression) during pregnancy are common. Various strategies such as hypnosis are available to reduce these symptoms. The objective of the authors in this study is to investigate the impact of a hypnosis intervention in reducing physical and psychological symptoms during pregnancy. A pre-test/post-test quasi-experimental design was employed in this study. The hypnosis intervention was given to the experimental group participants at weeks 16 (baseline), 20 (time point 1), 28 (time point 2), and 36 (time point 3) of their pregnancy. Participants in the control group received only the traditional antenatal care. Participants from both groups completed the Depression Anxiety Stress Scale-21 (DASS-21) and a Pregnancy Symptoms Checklist at weeks 16, 20, 28 and 36 of pregnancy. Results indicated that stress and anxiety symptoms were significantly reduced for the experimental group, but not for the control group. Although mean differences for the depressive symptoms were not significant, the experimental group had lower symptoms at time point 3. The physical symptoms’ results showed significant group differences at time point 3, indicating a reduction in the experience of physical symptoms for the experimental group participants. Our study showed that hypnosis intervention during pregnancy aided in reducing physical and psychological symptoms during pregnancy.